Regional strategic plan for malaria in the Americas 2006 - 2010 (PAHO Washington, D.C.US, 2006)
Provides a comprehensive analysis of the regional, sub-regional, and national situations; takes into serious account the strengths and weaknesses of existing institutions; and offers concrete and realistic solutions to combat malaria.
Keywords: MALARIA